Electrochemistry in Room-Temperature Ionic Liquids: Potential Windows at Mercury Electrodes - Rogers, E; Sljukic, B; Hardacre, C; Compton, R (2009)
The cathodic and anodic potential limits of eleven different ionic liquids were determined at a mercury hemisphere electrode. Ionic liquids containing the phosphonium cation (tri(n-hexyl)tetradecylphosphonium, [P14,6,6,6]+) give the largest potential window, especially when coupled to a trifluorotris(pentafluoroethyl)- phosphate, [FAP]-, or bis(trifluoromethanesulfonyl)imide, [NTf2]-, anion. © 2009 American Chemical Society.